Determination of optimal parameters of the pulse width modulation of the 4qs transducer for electriс rolling stock - Demydov Оleksandr; Liubarskyi, Borys; Domanskyi, Valerii; Glebova, Marina; Iakunin, Dmytro; Tyshchenko, Anna (Eastern-European Journal of Enterprise Technologies, 2018)
Operating modes of the single-phase 4qs transducer with pulse-width modulation as part of the AC electric rolling stock are investigated. The method is developed for determining the PWM parameters, at which the optimum transducer mode in terms of minimizing the reactive power in the “locomotive-traction network” system is implemented. The features of the developed method are the division of the process of determining the optimum PWM parameters into 2 steps. This allows removing unnecessary blocks from the simulation model and reducing the total simulation time. At the first step, the values of the power factor and current of the DC link in the whole range of coefficients of modulation and shift between the network current and the reference sine-wave signal are determined. Further, from the received data array, pairs of values of the PWM parameters, which ensure the highest power factor of the “electric locomotive-traction network” system are allocated and entered into the table system for setting the PWM parameters. At the second step, the dependences of power loss, and, consequently, both the efficiency and total harmonic distortion of the network current on the transducer clock frequency are determined. The determination of power loss is based on the calculation of the energy dissipated for 1 s on the IGBT transistor and snubber resistor depending on instant values of current through them